セッピョウ シリョウ ノ カガク カイセキ アルファセン ハコウ ブンセキホウ オ モチイタ セッピョウチュウ 210Pb ノ コウカンド ソクテイ - 鈴木, 利孝; スズキ, トシタカ; 太田, 一岳; オオタ, カズタカ; 藤井, 理行; フジイ, ヨシユキ; 渡辺, 興亜; ワタナベ, オキツグ; Suzuki, Toshitaka; Ohta, Kazutaka; Fujii, Yoshiyuki; Watanabe, Okitsugu (1996)
P(論文) 雪氷試料中の^<210>Pbは半減期22.3年の放射性核種であり, 大気エアロゾルの起源を考察するうえで, また, 氷河への堆積速度を推定するうえで有効な情報を与える。本報ではα線波高分析法を用いた氷中^<210>Pbの高感度分析法と氷コア年代決定法について紹介する。スバールバル諸島オスゴルド氷河で採取した氷コア試料について天然放射性核種^<210>Pbを測定した。^<210>Pbの放射能は, その娘核種である^<210>Po(半減期138日)から放出されるα線を計測することによって求めた。氷河表層における^<210>Pb濃度は110mBq/kgであり, 約30m深における4.72mBq/kgまで深さとともに指数関数的に減少した。30m以深で濃度はほぼ一定値を示し, 30mから180mまでの平均濃度は4.85±1.33mBq/kgであった。これらの結果は氷河上に降下した大気起源^<210>Pbが, その半減期に従って時間とともに放射能を減衰させていったことを示している。 The natural radioactive nuclide, ^<210>Pb, with a half-life of 22.3 years in snow and ice is useful for considering the origin of atmospheric aerosols and also for estimating the sedimentation rate onto a glacier. The α spectrometric method for sensitive analysis of ^<210>Pb in ice samples and the method of ice core dating are described in this paper. Measurements of ^<210>Pb in ice cores from the Arctic glacier, Åsgardfonna, in the Svalbard archipelagos have been made. The activity of ^<210>Pb was obtained by counting α rays from its daughter nuclide, ^<210>Po (half-life 138 days). The specific activity of ^<210>Pb at the surface of the glacier, 110mBq/kg, decreased exponentially with depth to 4.72mBq/kg at about 30m depth. Below 30m, the activities were nearly constant and its average value from 30m to 180m was 4.85±1.33mBq/kg. The results indicate that the atmospheric ^<210>Pb deposit onto a glacier decays as a function of time at a rate controlled by its half-life. departmental bulletin paper